Handbook of affective sciences - Davidson, Richard J.; Scherer, Klaus R.; Goldsmith, H. Hill (Series in affective science., 2003)
This volume is a comprehensive roadmap to the burgeoning area of affective sciences, which now spans several disciplines. The Handbook brings together, for the first time, the various strands of inquiry and latest research in the scientific study of the relationship between the mechanisms of the brain and the psychology of mind. In recent years, scientists have made considerable advances in understanding how brain processes shape emotions and are changed by human emotion. Drawing on a wide range of neuroimaging techniques, neuropsychological assessment, and clinical research, scientists are beginning to understand the biological mechanisms for emotions. As a result, researchers are gaining insight into such compelling questions as: How do people experience life emotionally? Why do people respond so differently to the same experiences? What can the face tell us about internal states? How does emotion in significant social relationships influence health? Are there basic emotions common to all humans? This volume brings together the most eminent scholars in the field to present, in sixty original chapters, the latest research and theories in the field.; The book is divided into ten sections: Neuroscience; Autonomic Psychophysiology; Genetics and Development; Expression; Components of Emotion; Personality; Emotion and Social Processes; Adaptation, Culture, and Evolution; Emotion and Psychopathology; and Emotion and Health. This major new volume will be an invaluable resource for researchers that will define affective sciences for the next decade.